Semiotic Analysis of the Lelakaq Poetry of the Sasak Tribe as an Ethnolinguistic Study to Improve Students' Understanding of Concepts and Cultural Literacy - Damayanti, Sri; Khairunnisah, Noni Antika; Walmukmim, Sayyid Ahmad; Imron, Imron (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The Sasak people of Lombok Island, West Nusa Tenggara, are rich in oral traditions that have been passed down from generation to generation. One of these traditions is Lelakaq, a form of traditional poetry that embodies cultural values, history, and local wisdom. The aim of this study is to conduct a semiotic analysis of Lelakaq as an ethnolinguistic inquiry and to explore its implementation in learning practices. This research employed a descriptive qualitative approach. The participants included cultural leaders, community members, teachers, and students. Data collection instruments consisted of checklists, observation sheets, interview guidelines, and tests. Data were gathered by compiling Lelakaq poems from various sources, distributing response questionnaires, and conducting in-depth interviews to confirm and strengthen findings. In addition, tests were administered to evaluate students’ conceptual understanding and cultural literacy. Data analysis applied Barthes’ semiotic approach to the poems, narrative descriptive analysis for interviews and student responses, and simple statistical analysis for test results. The findings reveal that Lelakaq poetry of the Sasak community serves multiple functions: aesthetic, social, cultural, and educational. Semiotic analysis indicates that students found it easier to grasp denotative meanings compared to connotative ones, with an average score of 74.88 (Good category). Specifically, 32% of students achieved Excellent, 24% Good, 32% Fair, and 12% Poor. Triangulation of data highlights a generational gap in understanding cultural symbols, underscoring the need for creative strategies and integration of Lelakaq into learning processes to foster cultural literacy, strengthen local identity, and enhance conceptual comprehension